CLINICAL AND LABORATORY MANIFESTATIONS OF ALCOHOLIC LIVER DISEASE AT THE CIRRHOSIS STAGE ASSOCIATED WITH NON-ALCOHOLIC FATTY LIVER DISEASE DEPENDING ON DISEASE COMPENSATION - Matkovska, N.R.; Virstiuk, N.H.; Balan, U.V.; Kostitska, I.O.; Voloshynovych, M.S.; Chaplynska, N.V.; Rudnyk, V.T. (World of Medicine and Biology, 2022)
The purpose of the study was to clarify the features of course of alcoholic liver disease at the stage of cirrhosis in combination with fatty liver disease. Clinical, laboratory and instrumental examinations were performed for 204 patients with alcoholic liver cirrhosis. It was found that all patients systematically took toxic doses of alcohol that caused clinical manifestations of the disease and a violation of the functional state of the liver. Somatometric indices significantly differed in all patients depending on the degree of compensation. The thickness of the skin and fat fold are reliable indicators that reflect the state of the fat depot of the body; the circumference of shoulder muscles is a reliable indicator of the reduction of the somatic protein pool, accompanied by a decrease in the synthetic function of the liver, especially in patients associated with fatty liver disease. Therefore, when examining patients with alcoholic liver cirrhosis, along with general clinical and laboratory-instrumental examinations, it is recommended to evaluation the trophological status to predict the course of liver cirrhosis.